THE Curriculum : Everything You Need to Know to Be a Master of Business Arts - Bing, Stanley, (HARPER BUSINESS, 2014)
Bing explains how business works, and shows how that knowledge can be used to achieve power, happiness, and indefensible amounts of money. From fabricating a sustainable business personality to mastering electronic communications, and dealing with bosses and other crazy people, he shares his secrets-- along with an attractive diploma, suitable for framing.